(untitled) (International Nexus Multidisciplinary Research Journal, 2026)
This study investigated social media addiction and substance use as correlates of academic achievement among senior secondary school students in North West, Nigeria. Two (2) research objectives and hypotheses were stated and formulated to guide the study. A correlational research design was adopted for the study. The population comprised of four hundred and forty one thousand, three hundred and fourteen (441,314) SSII students and a sample size of one thousand five hundred and thirty two (1,532) senior secondary school students were drawn and a multi-stage sampling technique was adopted for the study. Three (3) instruments were used for collection of data from the respondents, Social Media Addiction Questionnaire (SMAQ), Substance Use Questionnaire (SUQ) and Mathematics Achievement Test (MAT). The instruments were validated by three (3) experts, two specialists in Educational Psychology and one in Test and Measurement and the reliability coefficients of 0.75 for social media addiction, 0.79 for substance use and 0.78 for mathematics achievement test were obtained respectively. The analysis employed Pearson Product Moment Correlation Coefficient (PPMC) for bivariate relationships and Multiple Regression Analysis for multivariate associations, all tested at a 0.05 level of significance. Key findings revealed that social media addiction and substance use had a relationship with academic achievement. Recommendations such as; school authorities should set clear policies limiting phone and social media usage during school hours to curb addiction and refocus attention of student on academics among others.